PENGARUH MANAJEMEN LABA DAN PERENCANAAN PAJAK TERHADAP NILAI PERUSAHAAN : PERAN MODERASI PROFITABILITAS: THE EFFECT OF EARNING MANAGEMENT AND TAX PLANNING ON COMPANY VALUE: THE MODERATION ROLE OF PROFITABILITY - Angelisa, Ellen; Zirman, Zirman; Odiatma, Fajar; Hanif, Rheny Afriana (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
This study's objective is to analyze the effect of earnings management and tax planning on the company's value, with profitability serving as a moderating variableIn this survey, the population is the manufacturing business that was listed on the Indonesia Stock Exchange between 2018 and 2020. 210 companies provided samples to us via a purposeful sampling technique. The study of data through multiple regression demonstrates that the management of earnings has no impact on business value. Tax planning, though, has an impact on corporate value. Profitability cannot moderate the effect of earnings management on firm value but profitability can moderate the effect of tax planning on firm value, this is because if the company is able to generate high profits then managers will try to do a good job of tax planning